Self-Control Outdoes Fluid Reasoning in Explaining Vocational and Academic Performance—But Does It? - Schmidt, Fabian T. C.; Lindner, Christoph; Etzel, Julian M.; Retelsdorf, Jan (Frontiers in Psychology, 2020)
Trait self-control, the ability to interrupt undesired behavioral tendencies and to refrain from acting on them is one of the most important socio-emotional skills. There had been some evidence that it outperforms intelligence in predicting students’ achievement both measured as school grades and standardized achievement tests. However, recent research has shown that the relationships between trait self-control and measures of achievement are more equivocal emphasizing the importance of the respective outcome of the test to the individual. On the one hand, high-stakes school achievement measures such as GPA repeatedly showed strong relationships with trait self-control. On the other hand, findings on the relationships between trait self-control and performance in mostly low-stakes standardized achievement tests were more heterogeneous. The substantial positive relationship between intelligence and both achievement measures is uncontested. However, the incremental value of trait self-control beyond intelligence when investigating their relationships with achievement remains uncertain. To investigate the relationships of self-control with school achievement and two standardized achievement tests (school Mathematics and Physics) beyond fluid reasoning, we drew on a large heterogeneous sample of adults in vocational training (N = 3,146). Results show differential patterns of results for fluid reasoning and trait self-control and the achievement measures. Trait self-control and fluid reasoning showed similar relationships with school achievement, whereas only fluid reasoning was significantly associated with standardized achievement test scores. For both achievement measures, no significant interaction effects between trait self-control and fluid reasoning were found. The results highlight the utility of trait self-control for performance in high-stakes school assessment beyond fluid reasoning, but set limits to the overall value of trait self-control for achievement in standardized assessments—at least in low stakes testing situations.